Depot-medroxyprogesterone acetate (DMPA) and cancer: memorandum from a WHO meeting. (World Health Organization, 1993)
Depot-medroxyprogesterone acetate (DMPA) is a long-acting progestational contraceptive, which is administered by injection. It was developed in the mid-1960s, when it was seen as a method that would be particularly useful for women seeking reversible contraception who had difficulty taking a pill every day. DMPA has been shown to be a highly effective contraceptive, and it has proved acceptable in a variety of settings. The drug is licensed as a contraceptive in more than 90 countries and has been widely used in a number of them, such as Thailand and New Zealand. On a worldwide basis, the licensing, acceptability, and prevalence of use have been influenced by concern that DMPA may increase the risk of cancer. Cancer of the breast has been a particular concern. This Memorandum reviews comprehensively the results of toxicological tests in animals and epidemiological studies in humans concerning the carcinogenicity of DMPA.